Familiaris [large type] - Wroblewski, David (Thorndike Press Large Print Top Shelf, 2024)
"The story of the Sawtelle family and the remarkable dogs that carry the Sawtelle name. It is spring 1919, and John Sawtelle's imagination has gotten him into trouble, again. Now John and his newlywed wife, Mary, along with their two best friends and their three dogs, are setting off for Wisconsin's Northwoods, where they hope to make a fresh start, and, with a little luck, discover what it takes to live a life of meaning, purpose and adventure. But the place they are headed for is far stranger and more perilous than they realize, and it will take all their ingenuity, along with a few new friends, to realize their dreams."--Provided by publisher.